2014
DOI: 10.1098/rspb.2014.0117
|View full text |Cite
|
Sign up to set email alerts
|

The total burden of rare, non-synonymous exome genetic variants is not associated with childhood or late-life cognitive ability

Abstract: Human cognitive ability shows consistent, positive associations with fitness components across the life-course. Underlying genetic variation should therefore be depleted by selection, which is not observed. Genetic variation in general cognitive ability (intelligence) could be maintained by a mutation–selection balance, with rare variants contributing to its genetic architecture. This study examines the association between the total number of rare stop-gain/loss, splice and missense exonic variants and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…DNA methylation, which can be used to form an epigenetic biomarker of age acceleration, was associated with cognitive function in the LBC1936, but not cognitive decline over 3 years within old age (Marioni et al 2015a). Apart from cognitive function, the LBC studies showed that a faster running epigenetic clock is associated with earlier death (Marioni et al 2015b). …”
Section: Genetic Influences On Cognitive Level and Cognitive Changementioning
confidence: 99%
“…DNA methylation, which can be used to form an epigenetic biomarker of age acceleration, was associated with cognitive function in the LBC1936, but not cognitive decline over 3 years within old age (Marioni et al 2015a). Apart from cognitive function, the LBC studies showed that a faster running epigenetic clock is associated with earlier death (Marioni et al 2015b). …”
Section: Genetic Influences On Cognitive Level and Cognitive Changementioning
confidence: 99%
“…Empirical studies so far have failed to find evidence of a link between intelligence and rare variants [25]. These studies have often been limited in scope, with only CNVs or exonic regions being considered, or being limited in statistical power because all rare variants were treated as having the same direction of effect through the use of burden tests [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, a small initial study purporting to link IQ to rare genetic copy number variant (CNV) load was not replicated [9,10]. A recent exome (the parts of the genome that code for proteins) genotyping study did not find links of accumulated loads of rare variants to intelligence [11].…”
mentioning
confidence: 99%